Kebijakan Digitalisasi Pengelolaan Pasar Tradisional Kreneng di Kota Denpasar - Antarini, Lilik; I Made Yudhiantara (Faculty of Social and Political Science, 2024)
Market management is a crucial issue in the public sector, as the market serves as a focal point for regional economic growth. Policies regarding the management of traditional markets are essential efforts that must be implemented for improved governance. The Denpasar City Government oversees traditional market management through the Denpasar City Department of Industry and Trade (Disperindag). One of the markets under the management of PD Pasar Kota Denpasar is Kreneng Market, located at the eastern end of Denpasar City. The digitalization efforts at Kreneng Market, which has evolved into a Smart Heritage Market, align with the broader goal of transforming Denpasar into a smart city. The digital transformation at Kreneng Market begins with the introduction of a payment system in the traditional market environment, focusing on the interests of both traders and buyers. This study aims to examine the Digitalization Policy in Managing Traditional Markets at Kreneng Market in Denpasar. Qualitative research methods will be employed, utilizing the interactive model analysis technique as outlined by Miles, Huberman, and Saldana (2014). Data collection will be carried out through documentation, interviews, and observation. The research findings indicate that Perumda Pasar Kota Denpasar has implemented a digitalization policy to facilitate transaction processes for traders at Kreneng Market through the QRIS program, supporting the government's initiative to establish Denpasar as a Smart City. The implementation of the QRIS application has made it easier for traders to manage both incoming and outgoing transactions (cash in and out). However, many traders still prefer cash payments, citing the perception that they are faster. Based on these findings, further efforts are needed to optimize traders' understanding and participation in the digitalization process, to enhance the integration of digital solutions and support the development of a smart city in Denpasar.